2019
DOI: 10.3390/min10010019
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and Tectonic Setting of Ore-Associated Intrusive Rocks in the Baiyinnuoer Zn–Pb Deposit, Southern Great Xing’an Range (NE China): Constraints from Zircon U–Pb Dating, Geochemistry, and Sr–Nd–Pb Isotopes

Abstract: The Baiyinnuoer skarn Zn–Pb deposit, located in the Southern Great Xing’an Range, Northeast China, is the largest Zn–Pb deposit of the northern China, with a total reserve of 32.74 Mt at average grades of 5.44% Zn and 2.02% Pb. The Zn–Pb ore bodies are hosted in the Lower Permian Huanggangliang Formation. The results of zircon U–Pb geochronology show that the ore-associated granodiorite porphyry, granodiorite, and diorite were emplaced at 248 ± 1.3, 251 ± 1.8, and 249 ± 1.4 Ma, respectively. The granodiorites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Consequently, the Bainaimiao arc belt has been regarded as a Japan-style island arc [37,49,50], Andean-type continental margin arc [20,51], or exotic terrain [42]. In addition, there is controversy about the formation age of the Bainaimiao arc, suggested to be Middle Neoproterozoic [50,52,53] or Ordovician-Silurian [32,51,54,55].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the Bainaimiao arc belt has been regarded as a Japan-style island arc [37,49,50], Andean-type continental margin arc [20,51], or exotic terrain [42]. In addition, there is controversy about the formation age of the Bainaimiao arc, suggested to be Middle Neoproterozoic [50,52,53] or Ordovician-Silurian [32,51,54,55].…”
Section: Introductionmentioning
confidence: 99%
“…Among these deposits, Baiyinnuo'er is the largest skarn Zn-Pb deposit in this region with reserves of 32.74 Mt at average grades of 5.44% Zn, 2.02% Pb, and 31.4 g/t Ag (Zeng et al 2009;Shu et al 2013). Although many previous studies have been conducted focusing on the geology, geochemistry, geochronology, S-Pb isotopes, and fluid inclusions of the Baiyinnuo'er mineralization system (e.g., Zhang and Bao 1990;Zhang et al 1991;Zeng et al 2007Zeng et al , 2009Jia et al 2008;Niu et al 2008;Jiang et al 2011Jiang et al , 2017Shu et al 2011Shu et al , 2013Shu et al , 2017Yi et al 2012;Zhao et al 2020), the timing of the Zn-Pb mineralization remains unclear. Some authors suggested the Triassic granodiorite to be the causative intrusion of the Zn-Pb ores (e.g., Jiang et al 2011), while others believed that the mineralization occurred during the Jurassic (Wang et al 2019) or the Early Cretaceous (Zeng et al 2009).…”
Section: Introductionmentioning
confidence: 99%